Tracking mitochondrial viscosity in living systems based on a two-photon and near red probe. (21st October 2019) - Peng, Min; Yin, Junling; Lin, Weiying
Abstract : A two-photon fluorescence probe, Mito-V, with near-red emission to measure the viscosity changes of mitochondria in living cells and in vivo . Abstract : A two-photon fluorescent probe, Mito-V, was designed and prepared for sensing the viscosity changes of mitochondria. The systematic investigations demonstrated that the fluorescence emission at 634 nm increased about 22-fold from methanol to 99% glycerol, indicating high viscosity dependence. Notably, using the probe, the mitochondrial viscosity fluctuations have been successfully monitored not only in living cells but also in zebrafish and living mice.